Information security practice and experience : 13th International Conference, ISPEC 2017, Melbourne, VIC, Australia, December 13-15, 2017, Proceedings /: 13th International Conference, ISPEC 2017, Melbourne, VIC, Australia, December 13-15, 2017, Proceedings. (2017) - Unknown
No abstract available